Earthquake activity in the Torishima Rift and Sofu Seamount, and its relationship to the October 2023 tsunamis in Japan - Koichiro Obana; Aki Ito; Toshiya Fujiwara; Masayuki Obayashi; Kentaro Imai; Yasuyuki Nakamura; Kenta Yoshida; Noriko Tada; Tomoya Nakajima; Hiroyuki Matsumoto; Gou Fujie; Satoru Tanaka; et al. (Earth, Planets and Space)
Abstract An increase in seismic activity was observed near the Izu-Torishima and Sofugan islands in the Izu-Ogasawara arc of Japan in early October 2023. Several M6-class earthquakes occurred from October 3 to 6, and tsunamis were recorded on October 5 and 6, associated with M6-class normal faulting earthquakes. On October 8, tsunamis were observed without any significant earthquakes but accompanied by distinct T-phase signals. Analyses of T-phases, tsunami waveforms, and bathymetry surveys suggested that the October 8 tsunamis were linked to the volcanic activity at the Sofu Seamount, located west of Sofugan Island. However, the precise location of the entire activity and its connection to the tsunamis on October 5 and 6 remain unclear. We conducted earthquake observations near the Sofu Seamount from November to December 2023 using ocean bottom seismographs (OBSs). These observations revealed that seismic activity extended approximately 50 km in the NNW direction, from the Sofu Seamount to the Torishima Rift, a back-arc rift between the Izu-Torishima and Sofugan Islands. Although it is difficult to constrain the hypocenter depths owing to the limited number of OBSs and their large separations, earthquakes in the Torishima Rift were likely located at depths of 15–20 km or even shallower, at approximately 5 km. The tsunami observed at Hachijo-jima Island on October 5 can be attributed to the rupture of a normal fault in the Torishima Rift, as inferred from OBS observations. Shallow normal faults and intrusions reaching the seafloor were previously imaged in the back-arc rift zone near the Torishima Rift. Moreover, the earthquake activity in early October showed a northward migration from the Sofu Seamount to the Torishima Rift, followed by a rapid decrease after the volcanic activity of the Sofu Seamount, which was accompanied by tsunamis on October 8. The results suggest that the seismic activity in early October 2023, accompanied by tsunamis, is likely related not only to the volcanic activity at the Sofu Seamount but also to the tectono-magmatic activity in the Torishima Rift. Graphical Abstract